A Unique Case of Extraovarian Sex-Cord Stromal Fibrosarcoma, With Subsequent Relapse of Differentiated Sex-Cord Tumor. (July 2015) - Wang, Jayson; Papanastasopoulos, Panagiotis; Savage, Philip; Smith, James Richard; Fisher, Cyril; El-Bahrawy, Mona A.
<x xml:space="preserve">Abstract</x> Primary fibrosarcoma arising from ovarian sex-cord stroma is a very rare neoplasm, with only a few reports in the literature. These tumors have been reported to express inhibin which allows their distinction from fibrosarcomas of soft tissue. Here, we report a case of a fibrosarcoma arising in the broad ligament. Despite being totally separate from the ovary, the tumor was diagnosed as sex-cord stromal type on the basis of inhibin expression. Furthermore, this patient suffered a recurrence of her tumor in the pelvis, which showed both the fibrosarcomatous, as well as other sex-cord elements, confirming the sex-cord stromal differentiation of the sarcoma. To our knowledge, this is the first case of a sex-cord stromal fibrosarcoma arising from an extraovarian site. Furthermore, this is also the first case of a recurrent fibrosarcoma, which showed redifferentiation of the tumor into other sex-cord components.